Prevalencia y factores asociados a la pediculosis en el Centro de Educación Inicial Fiscal María Franco de Carrillo, en el período lectivo 2012 - 2013. - Sarango Sánchez, Edwin R. (2013)
This research was conducted to determine the prevalence and factors associated with pediculosis caused by head lice (Pediculus humanus capitis) and developed in kindergarten Franco Maria Carrillo at the beginning of the 2012-2013 school year , a population of 219 students (103 males and 116 females) between the ages of 3-5 years. Ectoparasitológico diagnosis was performed by direct observation using a comb to detect the parasite complemented by surveys to obtain data such as age, gender, overcrowding, and hair characteristics when sharing cleaning implements